PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP KINERJA PERUSAHAAN - Rowina Kartika Putri; Dul Muid (Diponegoro Journal of Accounting, 2017)
This study aimed to examine the effect of corporate governance mechanism on company’s performance. The company’s performance in this study using the return on asset (ROA) and return on equity (ROE) on companies listed in the Indonesia Stock Exchange. Implementation of good corporate governance is a concept that emphasizes the importance of shareholder rights to obtain information with true, accurate, and timely. In the company that their corporate governance is not running well, could make gap between information that stated in financial statement and fact that happen in company. Corporate governance mechanism is expected to minimize the agency problem, so the company’s performance can be increase.The data that used in this research is secondary data, that the financial statements and annual reports of 74 companies listed on the Indonesia Stock Exchange in 2013-2015. The sampling method used in this study was purposive sampling method. The total number of samples in this study were 163 research samples. This study used multiple linear regression as analysis instrument. However, before doing the regression test, it’s examined by using classical assumption test.The results of this study indicate that the independence of the board of commissioners is negative effect and significantly effect on the firm’s performance both ROA and ROE. From this study, board size and the frequency of commisssioners meeting are significant positive effect on firm performance both ROA and ROE.